MSMEs Innovation Strategies during the COVID-19 Pandemic by Tofu Producers in Trunan Village, Magelang City - Panji Kusumo Prasetyanto; Rian Destiningsih; Jalu Aji Prakoso (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
The role of Micro, Small, and Medium Enterprises (MSMEs) as a driving force for the nation's economy has weakened when faced with the COVID-19 pandemic. It is estimated that 50 percent of the total business operators in micro and small businesses went bankrupt during the pandemic. A community service program is needed to encourage MSMEs to survive and develop at this time. No exception, MSME players in Magelang City who are engaged in tofu production in Trunan Village are facing a decrease in production scale due to COVID-19 and need assistance through community service activities. This service activity was carried out with a blended approach between offline and online to reduce the risk of the COVID-19 transmission but still be productive during the pandemic. Field identification was carried out as an initial step to find out the problems faced by tofu producers. The problem faced by tofu producer in Trunan Village is the low innovation of tofu products and the weak use of business information systems, which results in weakening tofu production. The low level of tofu product innovation causes the final product to be marketed only in conventional markets and does not have a target end-consumer. The sales information system was implemented to encourage the sale of tofu and derivative products to the public with a wider market reach. The implementation of this service refers to the two problems faced by MSME players by determining the main achievements in the form of MSME innovation strategies during the COVID-19 pandemic